Downregulation of CFTR Is Involved in the Formation of Hypertrophic Scars - Zhou, Yiwen (Biomed Res Int, 2020)
Hypertrophic Scars (HTSs) are a complex fibroproliferative disorder, and their exact mechanism is still not fully understood. In this study, we first found that cystic fibrosis transmembrane conductance regulator (CFTR) expression was downregulated in human hypertrophic scars at the RNA and protein levels by microarray data analysis, RT-PCR, and immunofluorescence (IF) staining. To validate that this downregulation of CFTR is involved in the formation of HTSs, we then applied a mechanical overloading intervention in both wild type and CFTR-mutant mice (ΔF508). Our results showed thatΔF508 mice exhibited delayed wound healing and a significantly larger HTS on day 28. Masson staining revealed that there was more collagen deposition in the HTS, and Sirius red staining and IF staining showed a higher ratio of collagen 1/collagen 3 (Col1/Col3) in ΔF508 mice. Real-time RT-PCR showed that the proinflammatory markers were higher in ΔF508 mice in all phases of scar formation, whereas the proliferation marker was similar. Moreover, we harvested the fibroblasts from both mice. Western blotting showed that the expression of Col1 was the same in both mice, and the expression of Col3 was significantly lower in ΔF508 mice. However, in a mechanical overloading condition, the expression of Col1 was significantly higher in ΔF508 mice, and the expression of Col3 was the same in both mice. Taken together, our results indicate that the downregulation of CFTR might affect the function of fibroblasts, resulting in a lower level of collagen type 3 and a higher ratio of Col1/Col3, and thus aggravate the formation of HTSs in mechanical overloading conditions.